Konstruksi Kalimat pada Dialog Film Rumah Tanpa Jendela Karya Aditya Gumay - Sri Maharani, Ni Made; Satyawati, Ni Made Sri; Putrayasa, I G.N.K. (Humanis, 2019)
The study entitled “Konstruksi Kalimat Pada Film Dialogue Rumah Tanpa Jendela karya Aditya Gumay”. The purpose of this study is to describe the structure, type, and meaning of the sentence in Film Dialogue Rumah Tanpa Jendela. The theoretical basic used in this study is structural theoryaccording to Verhaar (2012) and is supported by operational approaches in semantic cognitive, connotative,  and emotive meaning. The method and technique used to collect data in this study is the method refer to thenote taking technique. At the stage of presenting the results of data analysis, the method used is ushed. At the stage of presenting the results of data analysis informal and formal methods are used.The results of this study are foundin the structure of single sentences and compound sentences divided into two sentence patterns, namely single sentence patterns and compound sentence patterns. Single sentence pattern consist of SPO type, SPKet type, SPOKet type, SPPel type, PO type, POKet type, SP type, PS type, Pket type, and PSKet type. Compound sentence patterns consist SPKe+Pket type, SP+SPKet type, SPKet+SP type, SP+SketPO type, PKet+SPKet type, SPKet+Pket type, Konj+SP+SPO, and SP+SP type. Type of sentence based onthe nuber of clauses based on syntatic form, basedon the internal struture ofthe main clause, based on the presence or absence of changes in exclusion, based on syntactic functions.